THE EFFECT OF ARTIFICIAL INTELLIGENCE ON LOYALTY INTENTION IN BANKING SERVICES IN INDONESIA - Sari, Selly Mardiana; Masnita, Yolanda (Tekmapro, 2025)
This research was carried out with the aim of testing and analyzing the influence of perceived artificial intelligence on perceived Anthropomorphism, Interaction Quality, Confirmation, the impact of Perceived Anthropomorphism on Interaction Quality, Confirmation, the influence of Interaction Quality on Confirmation and Customer Experience, the influence of Confirmationaffects Customer Experience and the impact of Customer Experience on Loyalty Intention. The type of research used is quantitative research with research hypothesis testing. The sample collection method used purposive sampling with a sample of 218 respondents. The analysis tool used by SEM is using AMOS 23 software. The findings showed that Perceived Artificial Intelligence was proven to have a positive effect on Perceived Anthropomorphism, Confirmation, and Interaction Quality; perceived Anthropomorphism had a positive effect on Interaction Quality but was not proven to have a positive effect on Confirmation, Interaction Quality was proven to have an impact positive for Confirmation but not proven to have a positive effect on Customer Experience. Confirmation has been proven to affect Customer Experience positively, and Customer Experience has been proven to impact Loyalty Intention positively. The managerial implications in this study show that Artificial Intelligence is an essential variable in increasing customer loyalty in the form of digital banking services through the development of AI sensitive to user needs, namely through convenient service through application features that can improve the banking system's stability.